Assistance for the Introduction of Aquatic Sports through Swimkids in Early Childhood - Puspodari; Septyaning Lusianti; M. Anis Zawawi; Mokhammad Firdaus; Rendhitya Prima Putra; Nur Ahmad Muharram; Reo Prasetiyo Herpandika; Wing Prasetya Kurniawan; Irwan Setiawan; Rizal Agus Sebastian (Fakultas Olahraga dan Kesehatan, Universitas PGRI Banyuwangi, 2023)
Water activities (special swimming for those who are proficient) have many benefits. Can be compared, children learn to walk on the floor with children learning to swim directly. The different is that one is on the floor and theother is in the water. Children who learn to walk on the floor only a few motor muscles that move. While swimming all the motor muscles move. This means that children who learn to swim from a young age certainly have better motor skill. Physical improvent is more advanced in children who do not swim. Apart from being physical, swimming also stimulates more sctivr hormone, such as the hormone adrenaline. So that the end result, the level the end result, the level of intelligence can also be high. In development countries preschool aquatic sports progrsm are more focused. Introducing motormodeic aspect for basic swimming skills. Children are not taught to survive indepentently in the water and enjoy the activites they do. Swimming skil can be acquired more readily at the age of 5 years. Although some children younger that 4 years require longer introduction to learn swimming skill. Physically the child will succed in doing swimming movements after the muscle fibers and nerves are mature. The purpose of this community service activity is to share experiences in water activities for children from an early age, that is, between the ages of 1 – 4 years it will be better for children to learn quickly, and avoid the possibility of having an accident drowning in a pool. Through mentoring activities for the introduction of aquatic sports through swimkids in early childhood at the Sumber Alam Dawung Kediri swimming pool, it is hoped that it will be able to improve the quality of physical and mental health of young children, especially in the Kediri environmen